The essence and structure of professional (vocational) education schools methodologists’ professional competence - Gorban, Yevdokiya (Professional Pedagogics, 2018)
The article focuses on the need for substantiation the essence and structure of professional (vocational) education (P(V)E) schools methodologists’ professional competence with the purpose of updating the necessity for its development during the advanced studies intercourse period, and a brief analysis of the latest scientific papers and publications on the studied problem is done. Key concepts are interpratated according to native and foreign scientific thought: «competence», «essence», «structure», « professional (vocational) education schools methodologists «, «professional competence». Based on scientific researches analysis and generalization it has been established that the professional competence is considered as professional training and pedagogical workers’ (methodologists’) ability to perform tasks and activity responsibilities, the measure of corcondance and a crucial criterion of their eligibility to professional activity requirements that consists of the following components: knowledge, skills, professional position, a person’s individual psychological constitution and acmeological factors (values and need for self-development). The author analyzes the essence and structure of P(V)E schools methodologists’ professional competence. The key point of professional competence is revealed and the structure of pedagogical competence is given. It emphasizes the problem of the need for developing a teacher’s professional capability to creative work. It is pointed out that there is the modern society’s crucial need in educators-researchers able for innovative-based activity performing. The must of methodologists’ professional competence development is grounded and its content is revealed. The essence and structure of the concept «a methodologist’s professional competence» are specified. Major interrelated and interdependent structural components of the following professional competence ...